3D printing of bone and cartilage with polymer materials - Fan, Daoyang; Liu, Yafei; Wang, Yifan; Wang, Qi; Guo, Hao; Cai, Yiming; Song, Ruipeng; Wang, Xing; Wang, Weidong (Frontiers in Pharmacology, 2022)
Damage and degeneration to bone and articular cartilage are the leading causes of musculoskeletal disability. Commonly used clinical and surgical methods include autologous/allogeneic bone and cartilage transplantation, vascularized bone transplantation, autologous chondrocyte implantation, mosaicplasty, and joint replacement. 3D bioprinting technology to construct implants by layer-by-layer printing of biological materials, living cells, and other biologically active substances in vitro, which is expected to replace the repair mentioned above methods. Researchers use cells and biomedical materials as discrete materials. 3D bioprinting has largely solved the problem of insufficient organ donors with the ability to prepare different organs and tissue structures. This paper mainly discusses the application of polymer materials, bioprinting cell selection, and its application in bone and cartilage repair.